JURIDICAL REVIEW OF THE ARRANGEMENT AND IMPLEMENTATION OF CERTAIN TIME WORK AGREEMENTS IN LAW NUMBER 6 OF 2023 CONCERNING JOB COPYRIGHT AND LAW NUMBER 13 OF 2003 CONCERNING EMPLOYMENT - Etty Uyun; Henry Aspan; Dahlan (CV. RADJA PUBLIKA, 2024)
Law Number 6 of 2023 concerning Job Creation, there are changes to the provisions related to certain time work agreements (PKWT) which were previously regulated in Law Number 13 of 2003 concerning Employment. Law Number 6 of 2023 concerning Job Creation then experienced rejection from many workers because there were several changes to the provisions regarding fixed-term work agreements (PKWT) which were feared to result in changes to the time period within which a fixed-term work agreement (PKWT) could be entered into, the duration of which was determined. by a work agreement and is not regulated regarding the maximum limit in the law. The formulation of the problem in this research is, How does the regulation of fixed-term work agreements in Law Number 6 of 2023 and Law Number 13 of 2003 compare? What are the problems faced regarding the implementation of fixed-term work agreements after the enactment of the Job Creation Law? ?, This research uses a normative juridical method with a statutory approach and a conceptual approach. The data used is secondary data consisting of primary legal materials, secondary legal materials and tertiary legal materials. The results of this research concern regulations and implementation as well as issues regarding fixed-term work agreements in Law Number 13 of 2003 concerning Employment and after the enactment of the Job Creation Law.